Seroprevalence of SARS-Coronavirus 2 among asymptomatic healthy blood donors from healthcare and non-healthcare settings: Implications for safety of blood donors and blood collection staff during blood donation. (June 2021) - Pandey, Hem Chandra; Dhiman, Yashaswi; C.S., Chippy; Coshic, Poonam; Jain, Pankaj
Abstract: Introduction: SARS-Coronavirus-2 pandemic has adversely affected blood supply as potential blood donors were afraid of acquiring infection in hospital settings. We aimed to compare COVID-19 seroprevalence among asymptomatic blood donors from healthcare and non-healthcare setting to analyse the difference in exposure level of each group as well as the risk of acquiring infection during the process of blood donation. Material and Methods: Analysis of whole blood donors tested for SARS-CoV-2 IgG antibodies was carried out after categorizing them into healthcare workers (HCW) and non-healthcare workers (NHCW). NHCW were further categorized into residents of containment and non-containment zones and seroprevalence analyzed. Seroprevalence among different ABO blood groups was also analyzed. Results: 1191 blood donors were tested for SARS-CoV-2 antibodies with 9.5 % seropositivity. Significantly lower seropositivity of 3.2 % (p < 0.001) was observed among HCW as compared to 10.9 % seropositivity in NHCW. Among NHCW no difference in seropositivity was observed based on residence in containment or non-containment zone. Significantly higher (p = 0.012) seroprevalence was observed among A blood group donors (12.5 %) as compared to O blood group donors (6.8 %). Conclusion: Results suggests that a blood donor, in a hospital setting is less likely to be exposed to COVID-19 disease than when participating in activities of daily living. It is postulated that the lower seroprevalence among HCW as compared to NHCW reflects differences in knowledge and practice of preventive measures among these groups. The findings should instil confidence among blood donors and motivate them to donate blood without fear.